5 years of must reads from HBR. - HBR's 10 must reads 2019.; HBR's 10 must reads 2020.; HBR's 10 must reads 2021.; HBR's 10 must reads 2022.; HBR's 10 must reads 2023. (HBR's 10 must reads (Series), 2023)
Get the latest, most significant thinking from the pages of Harvard Business Review in 5 Years of Must Reads from HBR: 2023 Edition. Every year, HBR editors examine the ideas, insights, and best practices from the past twelve months to select the definitive articles that have provoked the most conversation and inspired the most change. From eliminating strategic overload, to persuading the unpersuadable, to the future of flexibility at work, the articles in this five-book collection will help you manage your daily challenges and meet the changing competitive landscape head-on. Books in HBR's 10 Must Reads series offer essential reading selected from the pages of Harvard Business Review on topics critical to the success of every manager. Each book is packed with advice and inspiration from leading experts, such as Michael Porter, Frances X. Frei, Marcus Buckingham, Adam Grant, Joan C. Williams, Roger Martin, Robert Livingston, and Katrina Lake. Company examples range from P&G, UPS, and Pfizer to Alibaba, Microsoft, and Stitch Fix. 5 Years of Must Reads from HBR: 2023 Edition brings the most current and important business conversations to your fingertips.